Faith Community Nursing and COVID-19: Creative and Inspired Practice. Issue 2 (April 2023) - Shackelford, Judy; Zimmerman, Wendy; Coleman, Kathleen; Henley, Lorie; Johnson, Betsy A.; Donovan, Laureen
ABSTRACT: A mixed-method, cross-sectional descriptive online survey was used to examine the impact of COVID-19 on faith community nurse (FCN) practice. The seven practice areas for FCNs provided a framework for a 20-question survey comparing their practice pre- and during COVID-19 was completed by 378 FCNs. The top five interventions during COVID were in the areas of spiritual support, health promotion, and advocating for services; a top need was peer support/networking. Creative strategies used to meet the faith community's needs were inspiring. Implications for practice adaptation are discussed.